Penggunaan Citra Sentinel 2A untuk Analisis Kemampuan Ruang Terbuka Hijau Dalam Menyerap Emisi Karbondioksida di Kota Denpasar - Marpaung, Nanda; Nuarsa, I Wayan; Diara, I Wayan (Nandur, 2022)
Denpasar City is a city that has the smallest percentage of area with the largest population on the island of Bali. Green open space in Denpasar City is estimated not to be able to accommodate the total carbon dioxide emissions generated by the population's energy consumption activities. The purpose of the study was to obtain the total area of green open space, total carbon dioxide emissions, and the ability of green open space to absorb carbon dioxide produced in Denpasar City. This research uses image analysis method and Tier-1 emission calculation method. The stages of the research include: literature study, data collection, sampling and analysis of the data that has been obtained. The results showed that the area of green open space in Denpasar City in 2016 was 3,615.14 ha and 3,031.45 ha in 2021. Total carbon dioxide emissions in Denpasar City were 1,021,061,707 tons/year in 2016 and 1,004,122,692. tons/year in 2021 based on the total consumption of electrical energy, premium fuel and diesel, and liquefied gas. The available green space capability in Denpasar City in 2016 is 210,609.38 tons/year/ha, and in 2021 it will be 176,605 tons/year/ha. The results of this study are expected to be used by the Denpasar city government as a study and reference in making policies related to the area of green open space and controlling carbon dioxide emissions.